Analisis Perilaku Pemeriksaan Payudara Sendiri (SADARI) pada Mahasiswi Fakultas Kedokteran Universitas Baiturrahmah - Melya Susanti; Resti Rahmadika Akbar; Rinita Amelia; Aulia J Anna Aprilia Meysa (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2022)
Breast self examination is one of the efforts to detect breast cancer early. This examination can find lumps or changes in the breast that could be a sign of a tumor or breast cancer that requires medical attention. To find out the description of breast self-examination behavior in students of the Faculty of Medicine, Baiturrahmah University class 2017. This study was descriptive categorical with a research design was cross sectional. The population of this study were students of the Faculty of Medicine, Baiturrahmah University with 87 samples using simple random sampling technique by following inclusion and exclusion criteria, the data was from a quiestionnaire and presented in a frequency distribution table. The results of data analysis obtained from respondens that (47.1%) had knowledge of breast self-examination, with sufficient category, (58.6%) had attitude category is good in breast self-examination, and (43.7%) perform breast self-examination for early detection of breast cancer. The respondens have sufficient knowledge about breast self-examination, have a good attitude about breast self-examination, and less than 50% perform breast self-examination for early detection of breast cancer.